Chronic kidney disease and the risk of cancer: an individual patient data meta-analysis of 32, 057 participants from six prospective studies. Issue 1 (December 2016) - Wong, Germaine; Staplin, Natalie; Emberson, Jonathan; Baigent, Colin; Turner, Robin; Chalmers, John; Zoungas, Sophia; Pollock, Carol; Cooper, Bruce; Harris, David; Wang, Jie; Mitchell, Paul; et al.
Abstract Background Chronic kidney disease (CKD) is an established risk factor for cardiovascular disease but the relevance of reduced kidney function to cancer risk is uncertain. Methods Individual patient data were collected from six studies (32, 057 participants); including one population-based cohort and five randomized controlled trials. Participants were grouped into one of five CKD categories (estimated glomerular filtration rate [eGFR] ≥75 mL/min/1.73 m2 ; eGFR ≥60 to <75 mL/min/1.73 m2 ; eGFR ≥45 to <60 mL/min/1.73 m2 ; eGFR <45 mL/min/1.73 m2 ; on dialysis). Stratified Cox regression was used to assess the impact of CKD category on cancer incidence and cancer death. Results Over a follow-up period of 170, 000 person-years (mean follow-up among survivors 5.6 years), 2626 participants developed cancer and 1095 participants died from cancer. Overall, there was no significant association between CKD category and cancer incidence or death. As compared with the reference group with eGFR ≥75 mL/min/1.73 m2, adjusted hazard ratio (HR) estimates for each category of renal function, in descending order, were: 0.98 (95 % CI 0.87–1.10), 0.99 (0.88–1.13), 1.01 (0.84–1.22) and 1.24 (0.97–1.58) for cancer incidence, and 1.03 (95 % CI 0.86–1.24), 0.95 (0.78–1.16), 1.00 (0.76–1.33), and 1.58 (1.09–2.30) for cancer mortality. Among dialysis patients, there was an excess risk of cancers of the urinary tract (adjusted HR: 2.34; 95 % CI 1.10–4.98) and endocrine cancers (11.65; 95 % CI: 1.30–104.12), and an excess risk of death from digestive tract cancers (2.11; 95 % CI: 1.13–3.99), but a reduced risk of prostate cancers (0.38; 95 % CI: 0.18–0.83). Conclusions Whilst no association between reduced renal function and the overall risk of cancer was observed, there was evidence among dialysis patients that the risk of cancer was increased (urinary tract, endocrine and digestive tract) or decreased (prostate) at specific sites. Larger studies are needed to characterise these site-specific associations and to identify their pathogenesis.